Ganoderma lucidum polysaccharides reduce methotrexate-induced small intestinal damage in mice via induction of epithelial cell proliferation and migration - Chen, Li-hua (Nature Publishing Group, 2011)
AIM: To study the effects of Ganoderma lucidum polysaccharides (Gl-PS) on methotrexate (MTX)-induced small intestinal damage in mice and the underlying mechanisms. METHODS: BALB/c mice were used for in vivo study. The mice were administered with Gl-PS (50, 100, or 200 mg/kg, ig) for 10 d, and injected with MTX (50 mg/kg, ip) on d 7 and 8 to induce intestinal damage, and then sacrificed on d 11 for morphological study and tissue malondialdehyde (MDA) and superoxide dismutase (SOD) measurements. Before sacrificing, blood samples were collected to analyze immunoglobulin A (IgA). Rat intestinal IEC-6 cells were used for in vitro study. Cell proliferation and migration were assessed using MTT method and an in vitro wounding model, respectively. Transforming growth factor β (TGFβ) protein expression was determined using ELISA assay. Ornithine decarboxylase (ODC) and c-Myc mRNA expression profiles were determined using RT-PCR. RESULTS: MTX treatment caused severe mucosal damage, significantly increased small intestine MDA levels, and decreased SOD and serum IgA levels in BALB/c mice. Gl-PS (100 and 200 mg/kg) markedly reversed the MTX effects. In IEC-6 cells, Gl-PS (0.1, 1, and 10 μg/mL) significantly stimulated the cell proliferation. Furthermore, Gl-PS (10 μg/mL) significantly stimulated the cell migration. In addition, Gl-PS (10 and 20 μg/mL) significantly increased the expression of ODC and c-Myc mRNAs. However, Gl-PS (up to 20 μg/mL) had no effect on the expression of TGFβ protein. CONCLUSION: The results suggest that Gl-PS protects small intestine against MTX-induced injury via induction of epithelial cell proliferation and migration.